Synthetic studies towards the cytotoxic marine natural product diazonamide A - Green, Clive P. (1999)
The thesis describes synthetic studies towards the marine natural product diazonamide A. This unprecedented compound was recently isolated from a colonial ascidian and displays exceptional levels of cytotoxic activity against human cancer cell lines. The Introduction includes an account of how diazonamide A was isolated and its structure determined. This is followed by a summary of the different natural products which have been isolated from ascidians, and highlights the structural similarities between these compounds and diazonamide A. The Introduction concludes with a review of structurally related natural products which concentrates on compounds containing oxazole rings or biaryl bonds.